Depression, anxiety and stress among dental undergraduate students; prevalence, stressors and relieving factors - Yaacob, Munirah; Harun, Nor Asilah; Ramli, Farizah; Abdul Razak, Hannah; Sajuni, Noor Aisyah (2017)
Aim: To investigate the depression, anxiety and stress, stressors and relieving factors among dental students at Kulliyyah of Dentistry (KOD).